2017
DOI: 10.1021/acsbiomaterials.7b00030
|View full text |Cite
|
Sign up to set email alerts
|

Uniform, Polycrystalline, and Thermostable Piperine-Coated Gold Nanoparticles to Target Insulin Fibril Assembly

Abstract: Because the process of insulin fibril assembly is linked to a multitude of medical problems, finding effective and biocompatible inhibitors against such an aggregation process could be beneficial. Targeting the aggregation-prone residues of insulin may perhaps work as an effective strategy to prevent the onset of insulin fibril assembly. In this work, we have synthesized uniform sized, thermostable gold nanoparticles (AuNPs piperine ) surface-functionalized with piperine to target amyloid-prone residues of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 54 publications
4
35
0
Order By: Relevance
“…But from our data, piperine might play a role in disintegrating the Aβ fibril formation. Recent studies reported that indirect involvement of piperine-coated gold formation was able to inhibit amyloid-prone residues of insulin (Anand et al, 2017, 2018). They found that the process of both spontaneous and seed-induced (misfolded protein aggregates) amyloid formation of insulin was strongly inhibited in the presence of piperine-coated gold nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…But from our data, piperine might play a role in disintegrating the Aβ fibril formation. Recent studies reported that indirect involvement of piperine-coated gold formation was able to inhibit amyloid-prone residues of insulin (Anand et al, 2017, 2018). They found that the process of both spontaneous and seed-induced (misfolded protein aggregates) amyloid formation of insulin was strongly inhibited in the presence of piperine-coated gold nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Although the UV–Vis absorption spectroscopy technique has verified the capability of phenolic acids to reduce metal ions, this method could not verify the attachment of phenolic acids to the surface of the synthesised NPs [91]. On the other hand, it is possible to detect characteristic absorbance peaks for capsaicin, cinnamic acid, gallic acid, salicylic acid, and other phenolic acids attached to the surfaces of metal NPs using Fourier‐transform infrared spectroscopy technique [50, 66, 68, 92]. Some other spectroscopic techniques have also been used for studying phenolic acid absorption on the surface of metal NPs.…”
Section: Mechanism Of Metal Nps Synthesis and Stabilisation By Phenmentioning
confidence: 99%
“…Gold nanoparticles, one of the earliest synthesized nanomaterials with superior electric, optical and mechanical properties [65,66], have attracted attention in nanodiagnostic and nanomedical applications due to their exquisite quantum size effect, surface effect, and macroscopic quantum tunneling effect. Thus far, various methods for the preparation of gold nanoparticles have been reported and reviewed [67][68][69], and many small molecule, DNA sequence, protein, bacterial, and virus detection methods have been developed based on gold nanoparticles. For example, Mirkin and his coworkers are the first team dedicated to the preparation and application of gold nanoparticles in biology and medicine, and they systematically reviewed the synthesis, modification and application of gold nanoparticles [70].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%